In the flesh [videorecording (DVD)] - Cranham, Kenneth, 1944-; Newberry, Luke (Warner Home Entertainment, 2013)
Zombie teenager Kieren Walker isn't comfortable in his 'undead' state. He didn't want to come back, he wanted to be dead. After his suicide four years ago, his friends and family thought they'd never see him again. But then, shortly after his funeral, thousands rose from the dead; and after a catastrophic war, imprisonment, months of rehabilitation and medication, the zombies are gradually being returned to their homes.